Resource‐to‐consumer ratio determines the functional response of an herbivorous fish in a field experiment. Issue 12 (28th September 2021) - Capitani, Leonardo; Roos, Natalia; Longo, Guilherme Ortigara; Angelini, Ronaldo; Schenone, Luca
Abstract : In theoretical ecology, the quantity of resource consumed by a consumer per unit of time, defined as functional response, is of paramount importance. To better understand species interactions over time it is necessary to analyze whether consumer's functional response depends on resource density alone (which is the reference assumption) or on both resource and consumer densities. There are few field studies that, by varying the resource and consumer densities, provide solid empirical evidence to indicate the most suitable model of functional response in complex systems, such as coral reefs. We performed a field experiment with an herbivorous surgeonfish and their resource, a red seaweed, in a near‐pristine reef ecosystem. We measured algal consumption while varying densities of consumers and resources. We fit nine alternative functional response models, which either included or excluded consumer‐dependence. The model selection and the parameter estimation indicated that the functional response of the herbivorous surgeonfish depended on the ratio of seaweed to herbivorous fish densities. These results imply that, within a given density, surgeonfish can share resources but individual's consumption rate decrease with higher fish densities. These results also suggest that mutual intraspecific interference exists at herbivorous fish densities generally observed in the field and it should be considered in predicting consumption rates by herbivorous reef fishes. Finally, this study indicates that models incorporating consumer‐dependence must be considered for understanding herbivorous fish and algae population dynamics when placed in the context of the most biodiverse ecological communities, such as reef ecosystems.